A review on bacteriocin extraction techniques from lactic acid bacteria - Isaac, Sharleen Livina; Mohd Hashim, Amalia; Faizal Wong, Fadzlie Wong; Mohamed Akbar, Muhamad Afiq; Wan Ahmad Kamil, Wan Nur Ismah (Springer, 2024)
Lactic acid bacteria (LAB) are widely known for the production of secondary metabolites such as organic acids and other bioactive compounds such as bacteriocins. Finding a broad application in food and healthcare, bacteriocins have received increased attention due to their inherent antimicrobial properties. However, the extraction of bacteriocins is often plagued with low yields due to the complexity of the extraction processes and the diversity of bacteriocins themselves. Here, we review the current knowledge related to bacteriocin extraction on the different extraction techniques for isolating bacteriocins from LAB. The advantages and disadvantages of each technique will also be critically appraised, taking into account factors such as extraction efficiency, scalability and cost-effectiveness. This review aims to guide researchers and professionals in selecting the most suitable approach for bacteriocin extraction from LAB by illuminating the respective advantages and limitations of various extraction techniques.